Answer:
10 ≤ x - 4
Step-by-step explanation:
Answer: (3x + 11y)^2
Demonstration:
The polynomial is a perfect square trinomial, because:
1) √ [9x^2] = 3x
2) √121y^2] = 11y
3) 66xy = 2 *(3x)(11y)
Then it is factored as a square binomial, being the factored expression:
[ 3x + 11y]^2
Now you can verify working backwar, i.e expanding the parenthesis.
Remember that the expansion of a square binomial is:
- square of the first term => (3x)^2 = 9x^2
- double product of first term times second term =>2 (3x)(11y) = 66xy
- square of the second term => (11y)^2 = 121y^2
=> [3x + 11y]^2 = 9x^2 + 66xy + 121y^2, which is the original polynomial.
Answer:
2/6 - 1/6 = k
Step-by-step explanation:
Answer:
A. 1
B. -1
C. 5
Step-by-step explanation:
A. Using the Formula, we get u sub 2 = 9-9+1, which is just 1
B. Using the Formula, we get u sub 3 = 1-3+1, which is equal to -1
C. Using the Formula, we get u sub 4 = 1-(-3)+1, which is just 1+3+1 = 5
It should be eight if I remember correctly